All in one: Leishmania major STT3 proteins substitute for the whole oligosaccharyltransferase complex in Saccharomyces cerevisiae - Nasab, Farnoush Parsaie (2008)
The transfer of lipid-linked oligosaccharide to asparagine residues of polypeptide chains is catalyzed by oligosaccharyltransferase (OTase). In most eukaryotes, OTase is a hetero-oligomeric complex composed of eight different proteins, in which the STT3 component is believed to be the catalytic subunit. In the parasitic protozoa Leishmania major, four STT3 paralogues, but no homologues to the other OTase components seem to be encoded in the genome. We expressed each of the four L. major STT3 proteins individually in Saccharomyces cerevisiae and found that three of them, LmSTT3A, LmSTT3B, and LmSTT3D, were able to complement a deletion of the yeast STT3 locus. Furthermore, LmSTT3D expression suppressed the lethal phenotype of single and double deletions in genes encoding other essential OTase subunits. LmSTT3 proteins did not incorporate into the yeast OTase complex but formed a homodimeric enzyme, capable of replacing the endogenous, multimeric enzyme of the yeast cell. Therefore, these protozoan OTases resemble the prokaryotic enzymes with respect to their architecture, but they used substrates typical for eukaryotic cells: N-X-S/T sequons in proteins and dolicholpyrophosphate-linked high mannose oligosaccharides.